Impact of atrazine on somatic aneuploidy in cupped oysters, Crassostrea gigas - Bouilly, Karine; Leitao, Alexandra; Mccombie, Helen; Chaves, R.; Guedes Pinto, H; Boudry, Pierre; Lapegue, Sylvie (Second B Chromosome Conference, 2004)
In the Pacific oyster, Crassostrea gigas hypodiploid aneuploid cells with 2n=19, 18 or 17 chromosomes have regularly been reported. There is a negative correlation between somatic aneuploidy and growth rate in oysters (Leitão et al., 2001a) as well as evidence for a genetic basis (Leitão et al., 2001b). Furthermore, non-random chromosome loss has been demonstrated in aneuploid karyotypes of C. gigas using the G-banding technique (Leitão et al., 2001c). This poster summarises different studies used to investigate the effects of the herbicide atrazine on the level of aneuploidy in this species